2018
DOI: 10.1590/0103-8478cr20170772
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic assisted extraction to obtain bioactive, antioxidant and antimicrobial compounds from marcela

Abstract: The aim of this study was to evaluate the effect of extraction conditions on bioactive compounds, as well as on antioxidant activity, and the antimicrobial activity of the extracts with the highest antioxidant characteristics. The extracts were obtained by conventional method and ultrasound-assisted extraction at various temperatures (20°C, 40°C and 60°C). Total phenolics, total flavonoids, antimicrobial activity and antioxidant activity were quantified by the methods of DPPH, FRAP, and ORAC, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The current research, on the other hand, demonstrated the effectiveness of aqueous extraction which is also known as a nonpolluting solvent for obtaining phenolic constituents. Many studies have been carried out in coffee, such as the optimum condition and extraction methods have been well explored, to attain maximum bioactive constituents with antioxidant potency from their raw materials ( Boeira et al, 2018 ; Santos et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The current research, on the other hand, demonstrated the effectiveness of aqueous extraction which is also known as a nonpolluting solvent for obtaining phenolic constituents. Many studies have been carried out in coffee, such as the optimum condition and extraction methods have been well explored, to attain maximum bioactive constituents with antioxidant potency from their raw materials ( Boeira et al, 2018 ; Santos et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported related to the total phenolic and flavonoid content of ciplukan using three different solvents (petroleum ether, ethyl acetate, and ethanol), the ciplukan extract using ethanol solvent had the highest content for total phenol and total flavonoid with values of 106.54 mg GAE/ g and 370.64 ± 4.33 mg QE/g, respectively [4]. In addition, study by [17] showed an increase in UAE temperature (20°C-60°C) directly proportional to an increase in total phenols and total flavonoids. The high total phenol and flavonoid obtained in this study (176.62 mg GAE/g and 121.33mg QE/g) indicated the effectiveness of UAE in attracting phenolic compounds present in the sample.…”
Section: Antioxidant Propertiesmentioning
confidence: 94%
“…The extraction time was set at 20 minutes in accordance with PIOVESAN et al (2017). Conventional and ultrasound-assisted extraction was performed according to BOEIRA et al (2018). For the extraction by the conventional method, an ultra-thermostatized bath (Marconi, model MA-184, São Paulo, Brazil) was used with constant shaker agitation (Marconi MA-039, São Paulo, Brazil).…”
Section: Methodsmentioning
confidence: 99%